Takhrij and Syarah Hadith about Chemistry: Prohibition of Wearing Gold for Men in Islam - Arief Iyustiana; Irsyad Nugraha; Tety Sudiarti; Ali Masrur; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the hadith of the Prophet SAW. about the use of gold jewelry for men. This research method is qualitative through takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this study are the dangers of wearing gold jewelry for men. The conclusion of this research is takhrij and syarah hadith of the Prophet. about the dangers of using gold for men that have a negative or harmful impact on health